2016
DOI: 10.1093/jisesa/iew035
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prophylactic Antibiotic Treatment: Effects on Survival, Immunocompetence and Reproduction Success ofParasemia plantaginis(Lepidoptera: Erebidae)

Abstract: Hundreds of insect species are nowadays reared under laboratory conditions. Rearing of insects always implicates the risk of diseases, among which microbial infections are the most frequent and difficult problems. Although there are effective prophylactic treatments, the side effects of applied antibiotics are not well understood. We examined the effect of prophylactic antibiotic treatment on the overwintering success of wood tiger moth (Parasemia plantaginis) larvae, and the postdiapause effect on their life-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…While the control larvae took longer to develop, once they reached adulthood, the emerging females were significantly heavier than the antibiotic-treated group ( figure 4 b ). This is congruent with previous findings where antibiotics were fed to pre-diapausing larvae of the wood tiger moth [ 67 ]. It is commonly accepted that heavier weight translates into greater fecundity [ 81 ], as was shown by Dickel et al [ 67 ], where heavier control females laid more eggs than females that had been feed with antibiotics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the control larvae took longer to develop, once they reached adulthood, the emerging females were significantly heavier than the antibiotic-treated group ( figure 4 b ). This is congruent with previous findings where antibiotics were fed to pre-diapausing larvae of the wood tiger moth [ 67 ]. It is commonly accepted that heavier weight translates into greater fecundity [ 81 ], as was shown by Dickel et al [ 67 ], where heavier control females laid more eggs than females that had been feed with antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…However, lytic and PO did not differ from the E. coli priming. By contrast, [ 67 ] reported a high PO activity in larvae that have been fed an antimycotic (fumagillin). [ 68 ] simulated ectoparasitism by implanting nylon threads on larvae and measured the encapsulation response (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…reproductive output) due to rate-limiting resources. It has been shown that smaller wood tiger moth females produce less eggs compared to larger ones [73]. This carried-over effect could have negative consequences to the adult phenotype via an underrepresentation of their genotype in the reproductive cohort and/or if the genotypes have reduced fitness compared to those from larger females.…”
Section: (B) Larva-adult Melanizationmentioning
confidence: 99%
“…Furthermore, sterile mealworms perform poorly, suggesting that the microbiota is required for the efficient digestion and detoxification of plant secondary products [76]. In other insects, antibiotic use can shorten the development time as well as reduce the number of eggs [77][78][79]. Although the treatment of edible insects with antibiotics could solve some of the problems discussed previously, the benefits are outweighed by the negative side effects in addition to the known problem of increasing the spread of antibiotic-resistant pathogens.…”
Section: Antibiotic Usementioning
confidence: 99%